Tibial Plateau Leveling Osteotomy in small and large breed dogs: a comparative retrospective study of complications and outcomes - Schuenemann, Riccarda; Kaczmarek, Jakub (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2023)
Objective To compare complication rates and outcomes of small and large breed dogs that had locking plate Tibial Plateau Leveling Osteotomy (TPLO) performed due to cranial cruciate ligament disease during the same time period at a single institution and identify potential influencing factors.Material and methods 136 cases with TPLO performed at a single institution between January 2013 and December 2015 were retrospectively reviewed. Dogs were grouped by plate sizes (2.0, 2.4, 2.7, 3.5 and 3.5 broad) and by small breeds (2.0–2.7 plate sizes) and large breeds (3.5 plates). Potential influencing factors on lameness and complications were recorded from the database and measured on radiographs and statistically compared.Results Small dogs experienced fewer complications than large dogs (10% vs. 22%) and not a single major complication. Small dogs were significantly less lame at recheck and at long-term follow-up. Progression of bone healing had an influence on the lameness grade of dogs at recheck after TPLO. Distance of the most proximal screw from the joint was identified as a risk factor for implant failure. The width of the patella ligament correlated with body weight and uniformly increased 2.4 times after TPLO.Conclusions TPLO in small breed dogs has a lower overall complication rate than in large breed dogs. The TPLO plate should always be placed as close to the joint as possible to reduce the risk of implant failure.Clinical relevance TPLO can be recommended as treatment for cranial cruciate ligament rupture (CCLR) in dogs of all sizes.
Keywords: TPLO; small breed dogs; implant failure; Synthes TPLO plates; patella ligament width; cranial cruciate ligament disease